Classification of Agricultural Pests Through Digital Images Using Deep Learning - de Oliveira Costa, Pedro Lucas; de Oliveira Costa, Thiago Matheus; Ferreira Rodrigues Moreira, Larissa; Furtado Pinto Silva , Leandro Henrique; Mari, João Fernando (Revista de Informática Teórica e Aplicada, 2025)
In the agricultural sector, pest detection is vital, and given the susceptibility of human analysis to errors, deep learning solutions such as Convolutional Neural Networks (CNNs) provide a promising alternative. Classifying insect pests is challenging due to the high variability among species across different regions and their various life stages. In this study, we evaluate several deep learning models and training strategies for automatic pest image classification. We analyze four CNN architectures—AlexNet, ResNet-50, EfficientNet, and Vision Transformer (ViT). Following a hyperparameter optimization step, the models were fine-tuned, and we examined the impact of four data augmentation strategies on classification performance using the Agricultural Pests dataset. ViT demonstrated superior performance, achieving an accuracy of 0.9574 without data augmentation. Although ViT did not benefit from data augmentation, these techniques proved essential for enhancing the performance of AlexNet, ResNet-50, and EfficientNet. Our findings underscore the potential of deep learning methods for pest classification, offering valuable tools to help professionals maintain crop quality and value.